Sadari: Skrining Anak Dasar Dengan Ape Dan Aktivitas Interaktif Pada Siswasiswi Sekolah Dasar di Kota Surabaya - Navyli, Syavira Ellen (Jurnal Global Ilmiah, 2025)
The purpose of this activity is to help students who have obstacles in the aspects of recognizing letters, spelling, reading, writing, difficulty maintaining focus, low emotional regulation and simple counting. As well as helping teachers to be able to identify students and students who need special treatment early on. The targets of this program are students of SDN Kebonsari I/414 Surabaya who receive special treatment. Activities are carried out in the classroom. The method used is Stimulus-Response Learning-based learning. The author approaches this with several methods, namely by providing APE (Educational Game Tools) and assessment sheets to record the results of students' abilities. The learning results show that students are enthusiastic about learning with a fun method, and the knowledge conveyed can be received well with repeated practice.